Correspondence of Julije Benešić with Poles. Letters from Maria Kuncewiczowa in the Collections of the Croatian Academy of Sciences (HAZU) - Dyras, Magdalena (Poznańskie Studia Slawistyczne, 2023)
Julije Benešć’s correspondence with Polish scholars, people of culture, writers, and numerous acquaintances and friends began in his school years and lasted until his death. A large collection of letters and postcards sent to him by Poles has been collected in the HAZU library in Zagreb, but unfortunately it has not yet been put in order, and some items have been lost. The materials in the collection were only collected in the form of a list prepared by Ivan Meden in 1978. This text presents letters from Maria Kuncewiczowa, which provide information about the relations of Polish writers with the Croatian popularizer of their works and about the writer’s perception of the Polish literary scene in the years 1920s.